Attitudes of Turskish Consumers toward Advertising through Sport among the Question how often Consumers purchase Sporting Goods - Gorica Zoric; Bojan Masanovic; Jovan Gardasevic (Journal of Anthropology of Sport and Physical Education)
Unlike other advertising mediums such as TV commercials or online advertising, people involuntarily receive sport advertisements; they prefer to watch the game for the sporting action than the regular advertisements. However, it is important to analyse their general attitudes among various questions, mostly due to the reason it varies from demographic group to demographic group. Hence, this research was aimed at gaining relevant knowledge about the attitudes of Serbian consumers toward advertising through sport among the question how often consumers purchase sporting goods. The sample included 173 respondents, divided into six subsample groups: consumers who do not purchase sport goods at all, then consumers who purchase sport goods less than ones a month, next 1–3 a month, 4–6 a month, 7–9 a month, as well as consumers who purchase sport goods more than 10 times a month. The sample of variables contained the system of three general attitudes which were modelled by seven-point Likert scale. The results of the measuring were analysed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the results it was concluded that significant differences occur at multivariate level, as well as between one of three variables at univariate level (p=.05). It is interesting to highlight that most of potential consumers (n=146) have recognized themselves in two categories: as consumers who purchase sport goods less than ones a month and one to three times a months, while there were no differences among the groups. If we take a look into previous investigations, it is interesting there are some opposite results, and the recommendations for further research are directed to spread out the sample a little bit more, mostly due to the reason the consumers who had a more negative attitudes were in the group that didn’t purchase the sport goods at all.